Hearing Status Among the Traffic Polices Of Dhaka Metrpolitan City - Islam, Md Saiful; Rahman, Md Asadur; Matin, Md Abdul; Arafat, Md Shahrior; Rahman, Chowdhury Md Mushfiqur (Journal of Dhaka Medical College, 2023)
Background: Noise induced hearing loss is a common and avoidable occupational hazards in urban environments. People in high noise area suffer from hearing impairment. They are considered as social burden in their late life. Identifying risk groups and providing them a safe occupational environment is the responsibility of welfare state. Aims and Objectives: To compare hearing between noise exposed traffic police with polices not exposed to high noise. Methods: A cross sectional study was conducted in Rajarbagh police line hospital from July 2015 to November 2016 where 180 police personnel were enrolled and divided into two groups for comparison with mean duration of work in police force 11.06 years in group-I and 10.48 years in group-II. Work hours of traffic police was 8 hours per day. Result: 37.7% of traffic police found to suffer from mild and 41.75% suffer from moderate degree of hearing loss that need attention of appropriate authority. Conclusion: Environmental pollution in Dhaka city is very high .High noise is a risk factors for occupational hazards that must be looked after by civil society and law enforcing agency to implement sound pollution act. J Dhaka Med Coll. 2022; 31(1) : 46-50